Interaction between Ground Squirrels with rattlesnakes in arid zones - Andrade-Ponce, Gabriel P.; Montero-Bagatella, Sandra H.; Durán-Antonio, Jessica; González-Romero, Alberto; Gallina, Sonia (Therya Notes, 2020)
The predation of ground squirrels by rattlesnakes has influenced the development of specialized anti-predatory strategies by squirrels. This note describes two cases of encounters of squirrels with rattlesnakes in México, captured photographically. The first event is the interac- tion between an individual of Xerospermophilus spilosoma and one of Crotalus atrox in the Mapimí Biosphere Reserve, Durango, an arid area of the Chihuahuan Desert in northern México. The second event involved two individuals of X. perotensis and one of C. scutulatus salvini in the Perote Valley, a semi-arid zone of Veracruz. Both squirrel species displayed anti-predation behaviors reported for the genus, as well as the abil- ity to spot snakes and communicate the alert status to other group members; thus, these observations contributes to the knowledge of the natural history of these species. Appendix